Visualisasi Data Penduduk Dalam Membangun E-government Berbasis Sistem Informasi Geografis (GIS) - Kurniawan Kurniawan; Darius Antoni (ISB Atma Luhur, 2020)
Kelurahan 16 Ulu is one of the areas in the city of Palembang which has an area of 475 Ha and consists of several RT. Citizen data collection is the main task of a RT head. The process of managing citizen data by the head of the RT at Kelurahan 16 ulu is still using manualmethod so to get and search information about citizen spread point and data mapping cost a lot of time cause the data still in family card, and the data not yet in mapping state. To solve this problem, it needs visually show the mapping based on Geographic Information System (GIS). GIS is able to manage data that have spatial references for purposes related to mapping and planning. The resulting mapping visualization is in the form of E-government based on GIS. So that it can help to find out the citizen spread point and improve effectiveness and performance in service to the citizen.